ANALISIS STRATEGI PENGEMBANGAN DIGITAL TOURISM SEBAGAI PROMOSI PARIWISATA DI TOBA SAMOSIR - Dewi Yanti (Jurnal Darma Agung, 2019)
The tourism sector is one sector that has great potential to increase state and regional revenues. For this reason, development is needed in developing tourism in Indonesia. One program from the government to increase the number of tourists is to prioritize tourism development in 10 new Bali tourist destinations and one of them is Tourism in Lake Toba. Toba Samosir Regency is one of the districts located around the Toba Lake area that has interesting tourist objects and it can be visited by tourists. Utilizing information technology as a medium of promotion through digital tourism can increase the number of tourist visiting to the area. The purpose of this research is to see and analyze the development of digital tourism in Toba Samosir as one of the ways to develop tourism in Toba Samosir. The analytical method used in this study is the SWOT analysis method by looking at internal factors (strengths and weaknesses) and external factors (opportunities and security) calculated in the development of digital tourism at Toba Samosir. The results of this study can be used by the government or related parties in determining the direction of tourism development in digital tourism.